Mapping plasmon-enhanced upconversion fluorescence of Er/Yb-doped nanocrystals near gold nanodisks. Issue 21 (20th May 2019) - Aigouy, Lionel; González, Maria-Ujué; Lin, Hung-Ju; Schoenauer-Sebag, Mathilde; Billot, Laurent; Gredin, Patrick; Mortier, Michel; Chen, Zhuoying; García-Martín, Antonio
Abstract : Fluorescence enhancements near metallic nanostructures have been directly mapped with a single nanocrystal attached at the end of a tip. Abstract : Fluorescence enhancement effects have many potential applications in the domain of biochemical sensors and optoelectronic devices. Here, the emission properties of up-converting nanocrystals near nanostructures that support surface plasmon resonances have been investigated. Gold nanodisks of various diameters were illuminated in the near-infrared ( λ = 975 nm) and a single fluorescent nanocrystal glued at the end of an atomic force microscope tip was scanned around them. By detecting its visible fluorescence around each structure, it is found that the highest fluorescence enhancement occurs in a zone that forms a two-lobe pattern near the nanodisks and which corresponds to the map of the near-field intensity calculated at the excitation wavelength. In agreement with numerical simulations, it is also observed that the maximum fluorescence enhancement takes place when the disk diameter is around 200 nm. Surprisingly, this disk size is small when compared to that yielding the highest far-field scattering resonance, which occurs for disks with a diameter of 300–350 nm at the same excitation wavelength. This shift between the near and far-field resonances should be taken into account in the design of structures in systems that use plasmon enhanced fluorescence effects.